2019
DOI: 10.14716/ijtech.v10i8.3471
|View full text |Cite
|
Sign up to set email alerts
|

Tofu Industrial Wastewater Treatment with Ozonation and the Adsorption Method using Natural Zeolite

Abstract: Tofu industrial wastewater is usually disposed of directly without undergoing waste treatment, a process that endangers the environment. The amounts of chemical oxygen demand (COD) and total suspended solids (TSS) in the wastewater exceed the maximum levels determined by the government of Indonesia. Ozonation and adsorption are well-known methods that can effectively degrade organic and inorganic compounds in wastewater. In this research, the removal of COD and TSS from tofu industrial wastewater was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Ozone exposure has excellent potential to inhibit the growth of mycelia growth and conidia germination. Ozonation has been proven to be a method to degrade and reduce the toxicity level of organic and inorganic compounds (Karamah et al, 2019). Moreover, ozone has fungitoxic and fungistatic activity, which is suitable for controlling anthracnose in papaya (Ong et al, 2013) and has also been observed in this study to have the same potential in chili.…”
Section: Quality Analysis 321 Quality Deteriorationsupporting
confidence: 59%
“…Ozone exposure has excellent potential to inhibit the growth of mycelia growth and conidia germination. Ozonation has been proven to be a method to degrade and reduce the toxicity level of organic and inorganic compounds (Karamah et al, 2019). Moreover, ozone has fungitoxic and fungistatic activity, which is suitable for controlling anthracnose in papaya (Ong et al, 2013) and has also been observed in this study to have the same potential in chili.…”
Section: Quality Analysis 321 Quality Deteriorationsupporting
confidence: 59%
“…The maximum increase in BOD/COD of 0.48 (Figure 3c) was attained after ozone pretreatment at a dose of 4 mg/min. Preliminary treatment with ozone provides some advantages for the removal of toxicity in dyes, destruction of aromatic and aliphatic acids , organic material, and enhancing biodegradability (Karamah et al, 2019;Suryawan et al, 2020a). A detention time of 120 minutes and an ozone dose of 4 mg/min yielded 91.6±0.8%…”
Section: Mbbr With Ozone Pre-treatmentmentioning
confidence: 99%
“…Tofu-processing wastewater treatment has also carried out by using combination of two-stage biological treatment with filtration system using river stone [11] and bioball [12] as media. Additionally, there are several methods applied for tofu industrial wastewater treatment, such as ozonation and adsorption method using natural zeolite [13], combination of coagulation and filtration methods [14], combination of Coagulation-Flocculation and Membrane [15], and also combination coagulationflocculation and ultrafiltration processes [16]. The use of sequencing batch reactor, and anaerobic baffled reactor using activated sludge were also applied to treatment of tofu wastewater [17,18].The purpose of this community service activity is the application of appropriate technology for treatment of wastewater in the tofu industry in Pekanbaru City with the combination of equalization processes (initial disposal and deposition processes), filtration and phytoremediation.…”
Section: Introductionmentioning
confidence: 99%